2022
DOI: 10.37934/arfmts.92.2.3648
|View full text |Cite
|
Sign up to set email alerts
|

The CFD Application in Analyzing The 024P108 Centrifugal Pump Damage as The Effect of High Vibration using Fluid Flow Discharge Capacity Parameters

Abstract: Petroleum is one of the natural resources that can produce energy both for fuel and for generating electricity. One of the most important and widely used equipment in this industry is a pump. A pump is a device for distributing fluids from one place to another. A centrifugal pump is a device for distributing move liquids from one place to another by converting the fluid's kinetic energy into potential energy through an impeller that rotates in the housing. The objective of this research is to analyze the dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results showed that the highest system energy efficiency was in the gas turbine generator unit 2.3 with 35.541% and exergy efficiency was 34.069%. The gas turbine generator component with the lowest exergy efficiency was the combustion chamber unit 2.2 with 76.81% and an exergy destruction of 92.581 MW [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the highest system energy efficiency was in the gas turbine generator unit 2.3 with 35.541% and exergy efficiency was 34.069%. The gas turbine generator component with the lowest exergy efficiency was the combustion chamber unit 2.2 with 76.81% and an exergy destruction of 92.581 MW [9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical methods for instance computational fluid dynamics (CFD) has widely used to solve free surface flow. CFD has been wide uses to solve free surface flow not only sloshing but also medical [1,2], marine engineering [3,4], mechanical engineering [5][6][7], Numerical study of floating breakwater was performed with CFD for calculation of transmission coefficient value [8]. Because free surface flow dealing with large discontinuities and deformation, meshfree CFD is suitable to apply.…”
Section: Introductionmentioning
confidence: 99%